2006
DOI: 10.1093/bja/ael237
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetist's responses to patients' self-reported drug allergies

Abstract: The majority of the self-reported allergies were in fact simply accepted adverse effects of the drugs concerned. The patients' reported drug 'allergy' history was generally well respected by anaesthetists and other medical staff. There were 13 incidents, mainly involving morphine, where patients were given a drug to which they had claimed a specific allergy. There were 101 incidents in 89 patients where drugs of the same pharmacological group as that of their allergic drug were used. There were no untoward rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 34 publications
4
29
0
3
Order By: Relevance
“…12 Details of the previous adverse drug events, including allergies, must be recorded. Making such an assessment will assist in correct decision making.…”
Section: Discussionmentioning
confidence: 99%
“…12 Details of the previous adverse drug events, including allergies, must be recorded. Making such an assessment will assist in correct decision making.…”
Section: Discussionmentioning
confidence: 99%
“…The current results support data previously reported by Lutomski et al [3] that showed significant discrepancies between medical records and in-depth allergy history taking. A similar study by MacPherson et al [5] clearly demonstrated that the patients’ self-reported drug allergies are unreliable and when taken as a fact they cause medical treatment to deviate from standard of care. Taken together, the data collected from the first part of the current study strongly suggest the need for better allergy history taking in order to eliminate overdiagnosis of drug allergy and distinguish between allergy, anticipated side effects and other nonrelated reactions.…”
Section: Discussionmentioning
confidence: 92%
“…Discrepancies between the medical records and meticulous allergy histories were common and the validity of reported allergic reactions was questionable. Incomplete documentation of the drug allergy status of a patient appears to be related mainly to deficient history taking and failure to distinguish between a clinical presentation suggestive of drug allergy and a simple adverse drug reaction, mostly related to the physician’s education rather than the patient’s ability to provide the information [4,5]. Various interventions have been suggested in an effort to improve the diagnosis of adverse drug reactions with suspected drug allergy (ADRSA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An added complication is that a patient's recollection of their allergy often does not tally with their medical records. 10,11 Spurious or incorrect penicillin allergy records can arise for several reasons: often, side effects from a previous course of treatment end up recorded as an "allergy" in a patient's record. The prevalence of penicillin allergy records that were attributable to nonallergic side effects has been reported to be between 16-50%, 12,13 with many of these patients able to safely tolerate the first line penicillin antibiotics after appropriate investigation.…”
Section: Introductionmentioning
confidence: 99%